Influence of Ageing on Selected Engineering Properties of Cassava [Manihot Esculenta (Crantz)] Roots (2014)
Postharvest processing of cassava roots is faced with problem of ineffective machines in Nigeria. Physiological changes associated with the common practice of leaving matured roots un harvested until when needed may affect their engineering properties which determine design parameters. Information on the engineering properties of cassava as affected by age, needed for appropriate machine design is scarce. This study was conducted to investigate the influence of ageing on some engineering properties of cassava roots. Three cassava varieties, TME 419, TMS 30572 and TME 7, were each harvested at 12, 15 and 18 Months After Planting (MAP). Root mass, length, diameter and peel thickness at the top, middle and bottom sections, Peel Proportion by Weight (PPW) and Moisture Content (MC) were determined. In addition, Coefficient of Friction (COF), Coefficient of Internal Friction (CIF), Coefficient of Rolling Resistance (CRR), and strength properties (stress, stiffness and toughness) were also determined at the ages. The COF and CRR were determined on Stainless Steel (SS), Galvanized Sheet (GS) and wood surfaces. All were done according to ASABE standards. Data were analyzed using descriptive statistics, regression and ANOVA at p = 0.05. Mass of TME 419 and TME 7 increased from 262.7±143.4 and 229.9±147.0 to 483.5±245.2 and 489.1±274.3 g between 12 and 18 MAP respectively, while TMS 30572 reduced after 15 MAP. Length and diameters of TME 419 and TMS 30572 reduced after 15 MAP while peel thicknesses increased with age. The TME 419 produced lowest PPW at 12 MAP and highest at 15 MAP while the moisture contents of roots ranged from 70.0% to 74.0% (wet basis). The COF of TMS 30572 across ages (12 to 18 MAP) ranged from 0.16 to 0.29, 0.42 to 0.53 and 0.61 to 0.79 on SS, GS and wood respectively. The TME 419 and TME 7 had the least COF on GS and wood at 15 MAP. The CIF peaked at 15 MAP for all the varieties. On all the surfaces, CRR peaked at 15 MAP for TMS 30572, decreased for TME 419, and decreased on SS and wood surfaces for TME 7, at this same age. The CIF decreased while COF increased with increase in MC. Age and MC significantly affected COF and CIF while peel significantly affected CRR. High COF on wood suggested high angle of inclination in wooden container design and storage structures. Low CRR implied that the roots would not slide but roll on all the surfaces. Peak stress, stiffness and toughness ranged from 0.41 to 1.30 N/mm2, 3.22 to 9.28 N/mm2 and 3.23 to 9.82 N.m respectively across ages and increased with increase in MC showing that roots require low power during processing. Influences of age and MC on the strength properties of TMS 30572 were not significant whereas TME 419 strength properties depended on age. Neither age nor MC significantly influenced the strength properties of TME 7. Root age and variety strongly influenced the engineering properties of cassava roots. Machine designers therefore need to take into consideration the properties of cassava roots across ages and variety for effective mechanical processing operations